Assessment of Croton lechleri vaginal toxicity in rabbits - Ayala, Salomón (2010)
Objective: To determine a Croton lechleri vaginal gel preparation toxicity in rabbits. Design: Experimental study. Setting: Alberto Guzman Barron Biochemistry and Nutrition Research Center, Clinical Research Institute, Institute of Pathology, Faculty of Medicine and Pharmacy Faculty, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological material: Croton lechleri resin and female white New Zealand rabbits. Methods: The animals were divided into three groups (n=5): I. Control, vehicle; II, C. lechleri 1%, and III, C. lechleri 5%; they received samples of 1 mL volume intravaginally 1 time/day for 10 consecutive days. The general clinical condition and physical appearance of the vagina and the perineum for signs of flow, erythema and edema were observed. At the end of the experiment surgical resection of the vagina of each rabbit was performed and signs of irritation, bleeding or mucosal damage were determined macroscopically. Specimens were placed in 10% buffered formalin and cervico-vaginal, mid-vaginal, and uro-vaginal samples underwent histopathology study. Main outcome measures: Vaginal irritation. Results: Gross examination of the vagina in both the control and the Croton lechleri 1% groups showed mild diffuse congestion. Two cases of Croton lechleri 5% formulation showed mild petechial congestion. Histopathology study revealed a vaginal irritation average score of respectively 3.4 to 6, and 3.6 to 8 for the 1% and 5% preparations. Conclusions: In our experimental conditions, gel preparations of C. lechleri evaluated were acceptable and not irritating to the vaginal mucosa.